Leverage Social Media Marketing to Increase Tourism: A Case Study of Lombok, Indonesia - Suleman, Dede; Styaningrum, Etik Dwi; Joesah, Nurzalinar; Nurhayaty, Ety; Yuliawati, Lilik; Sabil, Sabil (Dinasti International Journal of Management Science, 2024)
The rapid development of internet technology has had a significant impact impact on various sectors, including tourism. Social media, in particular, has emerged as a powerful one networking tools that bridge social and economic activities globally. This research examine the role of social media marketing activities (SMMA) in shaping tourists' intentions to visit Lombok, Indonesia, a popular destination known for its stunning views and rich cultural heritage. This research identify the main elements of SMMA such as interaction, trends, electronic word of word of mouth (e-WOM), and customization, and their impact on brand image and tourist visit intentions. Through a quantitative approach with survey from domestic and international tourists, this research reveals that SMMA significantly improve Lombok brand image and influences tourist intentions positively. These? findings provide valuable insights for tourism stakeholders to develop effective marketing strategies by utilizing social media? attract more visitors and promote Lombok as a must-visit destination.